CONCEPTIONS OF FARMER’S EARLY RETIREMENTS IN EU COUNTRIES AND IN POLAND AS THE INSTRUMENT OF THE AGRARIAN STRUCTURE IMPROVEMENT AND ACCELERATIONS OF THE EXCHANGE OF GENERATIONS - Tańska-Hus, Bożena; Orlewski, Marcin (Acta Scientiarum Polonorum. Oeconomia, 2002)
In context of the accession Poland must follow a process of the agriculture adjustment and of the agrarian legislation to the principles of the community rural policy. The one from standards of the acceptance to EU is the improvement of agriculture space structure according to the Council Directive No. 159 of 19 April 1972 in re of the improvement of area structure and the Council Regulation No. 797 of 12 March 1985 in re of the improvement of agrarian structure efficiency. The important instrument of the rural policy in a sphere of the agrarian transformations is initialing from 1 January 2002, with the Act of 26 April 2001 about structural pensions in the agriculture, the system of structural early retirements, which is leaning on the Council Regulation No. 2079 of 30 June 1992 (at present displaced by the Council Regulation No. 1257/99) with enactive the program of the financial assistance for trippant on the early retirement in agriculture.